Open-Label Randomized Controlled Trial to Assess the Efficacy and Safety of Triple Therapy With Aspirin, Clopidogrel, and Rivaroxaban Versus Dual Therapy With Aspirin and Clopidogrel in Patients With Acute Coronary Syndrome - Mahboob, Hafiz Mudabbar; Abid, Imran; Jalaludin, .; Jehangir, Hafiz Muhammad Sajid; Zahoor, Sarmad; Afzal, Muhammad Sohail (Biological and Clinical Sciences Research Journal, 2025)
Acute coronary syndrome (ACS) is a significant contributor to cardiovascular morbidity and mortality. This study aimed to evaluate the efficacy and safety of triple therapy with aspirin, clopidogrel, and rivaroxaban compared to dual therapy with aspirin and clopidogrel in patients with ACS. Methods: This open-label, randomized controlled trial was conducted at the Punjab Institute of Cardiology from May 2024 to October 2024. Ninety patients with ACS were randomized into two groups: the triple therapy group (n=45) receiving aspirin (75–100 mg daily), clopidogrel (75 mg daily), and rivaroxaban (2.5 mg twice daily), and the dual therapy group (n=45) receiving aspirin (75–100 mg daily) and clopidogrel (75 mg daily). The primary efficacy outcome was the incidence of major adverse cardiac events (MACE), including recurrent myocardial infarction, ischemic stroke, and cardiovascular death, assessed over three months. The primary safety outcome was the incidence of bleeding events, categorized according to the Bleeding Academic Research Consortium (BARC) classification. Secondary outcomes included medication adherence and quality of life, as measured by the EQ-5D. Results: At three months, the incidence of major adverse cardiovascular events (MACE) was lower in the triple therapy group (6.7%) compared to the dual therapy group (15.6%). However, the difference was not statistically significant (p = 0.18). Minor bleeding was more common in the triple therapy group (13.3% vs. 4.4%, p = 0.14), while significant bleeding was rare (2.2% vs. 0%, p = 0.31). Quality of life scores were comparable between groups (76.2 ± 6.8 vs. 74.5 ± 7.2, p = 0.28). Adherence rates were high in both groups (93.3% vs. 95.6%, p = 0.71). Conclusion: Triple therapy demonstrated a trend towards reduced MACE compared to dual therapy but was associated with an increased risk of minor bleeding. These findings highlight the need for individualized therapy in patients with ACS, particularly in the Pakistani population. Further large-scale studies are recommended to validate these results.